Achieving robust mainstream nitrite shunt at pilot-scale with integrated sidestream sludge treatment and step-feed. (1st September 2022) - Duan, Haoran; Watts, Shane; Zheng, Min; Wang, Zhiyao; Zhao, Jing; Li, Huijuan; Liu, Peng; Dwyer, Jason; McPhee, Paul; Rattier, Maxime; Larsen, Eloise; Yuan, Zhiguo; et al.
Highlights: Evaluation of two novel sidestream treatment-based strategies for nitrite shunt. Pilot-scale systems operated for >850 days to assess the process robustness. Solely alternating sludge treatment approach is challenged by NOB adaptation. Robust nitrite shunt process for 1 yr. by integrating sludge treatment and step-feed. Kinetic analysis suggests integrated strategy is key to robust nitrite shunt. Abstract: As a promising energy- and carbon efficient process for nitrogen removal from wastewater, mainstream nitrite shunt has been extensively researched. However, beyond the laboratory it is challenging to maintain stable performance by suppressing nitrite-oxidising bacteria (NOB). In this study, a pilot-scale reactor system receiving real sewage was operated in two stages for >850 days to evaluate two novel NOB suppression strategies for achieving nitrite shunt: i) sidestream sludge treatment based on alternating free nitrous acid (FNA) and free ammonia (FA) and ii) sidestream FNA/FA sludge treatment integrated with in-situ NOB suppression via step-feed. The results showed that, with sidestream sludge treatment alone, NOB developed resistance relatively quickly to the treatment, leading to unstable nitrite shunt. In contrast, robust nitrite shunt was achieved and stably maintained for more than a year when sidestream sludge treatment was integrated with a step-feed strategy. Kinetic analyses suggested that sludge treatment and step-feed worked in synergy, leading to stable NOB suppression. The integrated strategy demonstrated in this study removes a key barrier to the implementation of stable mainstream nitrite shunt. Graphical abstract: Image, graphical abstract